2020
DOI: 10.1111/cge.13805
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary stalk interruption syndrome broadens the clinical spectrum of the TTC26 ciliopathy

Abstract: Ciliopathies are a heterogeneous group of disorders, related to abnormal ciliary function. Severe biliary ciliopathy, caused by bi‐allelic mutations in TTC26, has been recently described in the context of a syndrome of polydactyly and severe neonatal cholestasis, with brain, kidney and heart involvement. Pituitary involvement has not been previously reported for patients with this condition. Pituitary stalk interruption syndrome (PSIS) is a congenital anomaly of the pituitary gland, diagnosed by characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…Features such as developmental delay, dysmorphic facial features, liver abnormalities, and cardiovascular disorders were similar to those reported previously [Shaheen et al, 2020]. More recently, pituitary stalk interruption syndrome has been reported in patients [David et al, 2020]. Pituitary hypoplasia was also reported in our patient; however, diabetes insipidus was not reported previously, and hydrocephalus has been reported in 1 of the 7 ciliopathies cases so far.…”
Section: Wgs and Sanger Sequencingsupporting
confidence: 90%
See 2 more Smart Citations
“…Features such as developmental delay, dysmorphic facial features, liver abnormalities, and cardiovascular disorders were similar to those reported previously [Shaheen et al, 2020]. More recently, pituitary stalk interruption syndrome has been reported in patients [David et al, 2020]. Pituitary hypoplasia was also reported in our patient; however, diabetes insipidus was not reported previously, and hydrocephalus has been reported in 1 of the 7 ciliopathies cases so far.…”
Section: Wgs and Sanger Sequencingsupporting
confidence: 90%
“…Using WES, Shaheen et al [2020] identified 3 homozygous variants (c.695A>G; c.4-1G>C; c.1238C>T) in the TTC26 gene of 7 different families in Saudi. Recently, David et al [2020] identified a homozygous missense variant, c.695A>G (p.Asn232Ser), in 2 Israeli families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 The four Israeli patients that were later reported displayed similar clinical features with additional pituitary gland and ocular findings, however, data on additional patients are needed to determine whether this represent a true difference between the populations. 7 On January 1, 2021, 1243 variants were cataloged in the INGD among Muslim Israeli Arabs 47 out of which were also reported in Saudi Arabia (3.8%). In many cases these were founder/assumed founder variants, but there were exceptions in both populations.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first report, five additional patients have been described, moreover, adding further clinical features, e.g. pituitary stalk interruption syndrome (Alfadhel et al, 2021; David et al, 2020). In 2021, the condition was named BRENS syndrome (MIM #619534) after its major clinical affections sites: Biliary, Renal, Neurological, and Skeletal (Alfadhel et al, 2021).…”
Section: Introductionmentioning
confidence: 99%